Druge SOSIALISASI TENTANG BAHAYA NARKOBA DI DESA RANTE BARU, KECAMATAN RANTEANGIN, KABUPATEN KOLAKA UTARA - Resqi Amelia; Arya Dirgantara; Muh. Alwi Suhajardita; Irmayanti; Reyna Zahra; Patma Cuanta; Besse Mifta; Mirna Wati; Wafiq Azizah; Bulan Purnama Sari; Samsuriadi; Siti Nurhafisah Rahmadani; Andi Aprizal; Muhammad Doni Ridwan; Muh Ali Rahmat (STKIP Subang, 2025)
Drug abuse and alcoholic beverages pose a serious threat to the health, safety, and future of young generations. This outreach activity aims to increase the understanding of students at MTS AN-NUR, Rante Baru Village, Rante Angin District, North Kolaka Regency, regarding the negative impacts of drug and alcohol abuse, as well as to prevent deviant behavior among adolescents. The methods used include material and media preparation, socialization, interactive discussions, and question-and-a oximately 50 students. The results indicate a significant improvement in students’ knowledge about the dangers of drugs and alcohol, the growth of awareness to reject substance abuse, and increased confidence in asking questions and participating in discussions. Moreover, this activity helped foster discipline, a sense of responsibility, and motivation among students to safeguard their future from drug abuse.